2011
DOI: 10.1039/c0mb00191k
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic approach to study parathyroid glands

Abstract: Parathyroid tumours are heterogeneous and in some cases the diagnosis may be difficult using histological features. In this study we used a two-dimensional electrophoresis (2D)/mass spectrometry (MS)-based approach to examine the global changes of parathyroid adenoma tissues protein profile compared to the parathyroid normal tissues. Validation of protein expression was performed by immunoblotting using specific antibodies. Ingenuity software was used to identify the biological processes to which these protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 61 publications
(60 reference statements)
4
37
3
Order By: Relevance
“…In order to make comparisons for the regulated proteins, a Venn diagram was created using the data provided by the earlier aforementioned studies and our data. ANXA2 and LMNA reported by Guisti et al, (12) and ATP5H reported by Varshney et al, (13) were also detected in our study.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In order to make comparisons for the regulated proteins, a Venn diagram was created using the data provided by the earlier aforementioned studies and our data. ANXA2 and LMNA reported by Guisti et al, (12) and ATP5H reported by Varshney et al, (13) were also detected in our study.…”
Section: Discussionsupporting
confidence: 76%
“…Bioinformatic analysis of the relevant pathways based on the regulated proteins predicted that 14-3-3 ζ/δ is the key protein in PA network. The study by Giusti et al,(12) demonstrated the use of a proteomic approach for the discovery of potential markers in differential diagnosis of PA. On this line of study, the later work by Varshney et al, (13) monitored the changes in parathyroid proteome in patients with sporadic parathyroid adenoma in comparison to normal parathyroid tissue. Fifteen differentially expressed proteins were reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, mutations were germline in two patients with CDKN1B mutations and in one carrying a mutation in AIP Contradictory results have been reported on the presence of CTNNB1 (encoding β-catenin) mutations involving serine/threonine phosphorylation 86,87 . Up to 30 proteins, involved in various cellular pathways (for example, response to biotic stimuli, cell organization and signal transduction), are differentially expressed in normal parathyroid and parathyroid adenomas 88 . Of these various proteins, 14-3-3ζ/ δ may be one of the key proteins in the pathogenesis of parathyroid adenoma.…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…Giusti and collaborators carried out comparative analysis to examine the changes in protein profile between adenomas and normal parathyroid tissue [77]. These authors verified the presence of 30 deregulated proteins in parathyroid adenomas, 22 of them being overexpressed when compared to normal parathyroid tissue [77].…”
Section: The Role Of Other Genes In Phptmentioning
confidence: 99%